Entamoeba histolytica Trophozoites and Lipopeptidophosphoglycan Trigger Human Neutrophil Extracellular Traps - Ávila, Eva E. (PLoS One, 2016)
Neutrophil defense mechanisms include phagocytosis, degranulation and the formation of extracellular traps (NET). These networks of DNA are triggered by several immune and microbial factors, representing a defense strategy to prevent microbial spread by trapping/killing pathogens. This may be important against Entamoeba histolytica, since its large size hinders its phagocytosis. The aim of this study was to determine whether E. histolytica and their lipopeptidophosphoglycan (EhLPPG) induce the formation of NETs and the outcome of their interaction with the parasite. Our data show that live amoebae and EhLPPG, but not fixed trophozoites, induced NET formation in a time and dose dependent manner, starting at 5 min of co-incubation. Although immunofluorescence studies showed that the NETs contain cathelicidin LL-37 in close proximity to amoebae, the trophozoite growth was only affected when ethylene glycol tetra-acetic acid (EGTA) was present during contact with NETs, suggesting that the activity of enzymes requiring calcium, such as DNases, may be important for amoeba survival. In conclusion, E. histolytica trophozoites and EhLPPG induce in vitro formation of human NETs, which did not affect the parasite growth unless a chelating agent was present. These results suggest that NETs may be an important factor of the innate immune response during infection with E. histolytica.